Social Benefits of Community-Based Tourism Activities in Betawi Setu Babakan Cultural Village, South Jakarta - Gagih Pradini; Anisa Putri Kusumaningrum; Fitri Agustiani (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Community participation is an indicator of success in community-based tourism, a tourism destination especially to include local communities in order to create collaboration and mutual benefits that synergize with each other. Betawi Setu Babakan cultural village is one of the popular destinations in Jakarta, because of its uniqueness, namely as a conservation of betawi culture in DKI Jakarta. community participation in betawi cultural villages is what must exist, researchers will see what social benefits the community gets in the pariwsata activities. In the Betawi Setu Babakan Cultural Village using qualitative research panels whether, in addition to using primary data researchers also use secondary data and literature studies to retrieve data